EFFICACY AND SAFETY OF DIODE-LASER TRANSSCLERAL CYCLOPHOTOCOAGULATION IN THE TREATMENT OF REFRACTORY GLAUCOMA - S.A.Boboev; S.S. Boboev; S.B. Khamrakulov; D.A. Abdullaeva (Scholar Express Journals, 2022)
This article presents the main methods of refractory glaucoma (RG) treatment. Surgical methods used for DH can be conventionally divided into two groups. The first one is fistulizing interventions, including traditional surgery, surgery with cytostatic preparations, and surgery with implants. The second group - cyclodestructive interventions suppressing secretory function of the ciliary body. Types of antiglaucoma drains are described, and the latest modifications of the valve drainage system are presented.
Keywords: Terminal Glaucoma; Contact Transscleral Diode-Laser Cyclophotocoagulation; Ciliary Body Atrophy